PENERIMAAN KRIM DENGAN PENAMBAHAN JAMUR TIRAM - MARHAENI PUTRI ADITYA (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2022)
This research is an experimental research aimed at knowing, the process of making oyster mushroom cream and acceptability of oyster mushroom cream, This research was conducted in the Laboratory of the Family Welfare Education Faculty of Engineering State University of Makassar. The data collection method used was documentation and score sheet. The data analysis technique used was Mean analysis, Anova difference test, and Duncan test. The results of this study indicated that the process of making oyster mushrooms cream includes preparation of materials and tools, weighing ingredients, washing of oyster mushrooms, steaming of oyster mushrooms, grinding of oyster mushrooms, and mixing the ingredients, the research result of organoleptic test of the preferred quality on the oyster mushroom cream product, formula F3 (10%) was choosen with the average color value is 5,56 (white), scent 5,19 (slightly fragrant), texture 5,06 (a bit soft), taste 5,50 (tasty), over all 5,8 (good), and the hedonic test 8 (like), formula F3 (10%) with acceptability 15 persons or 93,9% expressed like. ABSTRAKPenelitian ini adalah penelitian eksperimen yang bertujuan untuk mengetahui proses pembuatan krim jamur tiram dan penerimaan krim jamur tiram, Penelitian ini dilaksanakan di Laboratorium Pendidikan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Makassar. Metode pengumpulan data yang digunakan adalah dokumentasi dan angket (score sheet). Teknik analisis data yang digunakan adalah analisis mean, anova, dan uji duncan. Hasil penelitian ini menunjukkan bahwa proses pembuatan jamur tiram meliputi persiapan bahan dan alat, penimbangan bahan, pencucian jamur tiram, pengukusan jamur tiram, penghalusan jamur tiram, dan pencampuran bahan, hasil penerimaan uji organoleptik pada produk krim jamur tiram, menghasilkan formula terpilih yaitu F3 (10%) dengan klasifikasi warna 5,56 (putih), aroma 5,19 (agak harum), tekstur 5,05 (agak lembut), over all 5,8 (baik) dan uji hedonik 8 (suka). Formula F3 (10%) dengan penerimaan 15 orang atau 93,9% dinyatakan suka.